Kepailitan Akibat Pembatalan Pengesahan Rencana Perdamaian (Homologasi) Oleh Kreditor Separatis (Studi Putusan Mahkamah Agung No 177 K/Pdt.Sus-Pailit/2021): Kepailitan Akibat Pembatalan Pengesahan Rencana Perdamaian (Homologasi) Oleh Kreditor Separatis (Studi Putusan Mahkamah Agung No 177 K/Pdt.Sus-Pailit/2021) - Usak Usak (Journal of Innovative and Creativity, 2025)
In the case of PT Mopoli Raya, the Commercial Court at the Medan District Court issued a decision to ratify the Peace Agreement between PT Mopoli Raya (in PKPU) and its Creditors with Decision Number 17/Pdt.Sus-PKPU-Pengesahan Perdamaian/2020/PN Niaga Mdn, because it was deemed to have fulfilled the quorum as a condition for accepting the peace as regulated in Article 281 paragraph (1) letter b of Law Number 37 of 2004. However, PT Bank Maybank Indonesia Tbk, as a separatist creditor, considered that the ratification of the peace plan had not met the requirements and then filed an appeal. The purpose of this study is to examine the position of separatist creditors in the ratification of the peace plan and to analyze whether the Supreme Court Decision No. 177 K/Pdt.Sus-Pailit/2021 is in accordance with the provisions of Law Number 37 of 2004. The research method used in this study is the normative juridical method with a case approach. This study found that Law Number 37 of 2004 regulates the status of secured creditors in determining a reconciliation plan within the framework of a PKPU (Deferred Payment for Debt Obligations). One of these provisions is that secured creditors who disagree with the ratification of the reconciliation plan can file an appeal. Supreme Court Decision No. 177 K/Pdt.Sus-Pailit/2021 overturned the Commercial Court Decision at the Medan District Court, resulting in PT Mopoli Raya being declared bankrupt, in accordance with Law Number 37 of 2004.